2019
DOI: 10.1371/journal.pone.0218954
|View full text |Cite
|
Sign up to set email alerts
|

Animal behaviour in a human world: A crowdsourcing study on horses that open door and gate mechanisms

Abstract: Anecdotal reports of horses opening fastened doors and gates are an intriguing way of exploring the possible scope of horses’ problem-solving capacities. The species’ natural environment has no analogues of the mechanisms involved. Scientific studies on the topic are missing, because the rate of occurrence is too low for exploration under controlled conditions. Therefore, we compiled from lay persons case reports of horses opening closed doors and gates. Additionally, we collected video documentations at the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…A recent study based on anecdotal reports showed that horses are innovative in opening door and gate mechanisms (Krueger et al submitted, [49]), but experimental evidence for innovativeness in horses is still missing. The aim of this study was to establish whether 16 horses of mixed ages and breeds would show innovative behavior when confronted with an unfamiliar feeder.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study based on anecdotal reports showed that horses are innovative in opening door and gate mechanisms (Krueger et al submitted, [49]), but experimental evidence for innovativeness in horses is still missing. The aim of this study was to establish whether 16 horses of mixed ages and breeds would show innovative behavior when confronted with an unfamiliar feeder.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some equestrians voicing negative beliefs about science [48], within the equine community we are seeing increasing engagement with scientific research through media channels. Many printed and online lay publications contain synopses of recently published research, and citizen science approaches are gaining popularity with equine researchers providing another platform through which the equine community can engage with science, e.g., [49].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal [ 38 , 39 ] and depressive-like behaviour [ 27 , 40 ] may occur. Individuals’ attempts to mitigate such problems may stimulate innovations associated with movement, foraging, and social contact [ 11 , 41 43 ]. Animals may innovate out of need when the social environment is unstable and out of opportunity when it is stable [ 16 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental evidence may not reflect innovation seen in non-experimental contexts and typically experiments do not provide large datasets for studying individual and environmental effects on innovative behaviour. For this reason, we used crowd-sourcing methods when searching for cases where equids developed innovative behaviour in human management [ 41 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation